1971
DOI: 10.1002/pol.1971.160091101
|View full text |Cite
|
Sign up to set email alerts
|

Self‐oscillation mechanism of necking on extension of polymers

Abstract: A new phenomenon in necking of some polymers, including poly(ethylene terephthalate) (PETP) was detected. It was found that extension of PETP films under certain conditions results in periodic stress oscillations and a periodic change in appearance of the sample. The conditions at which self‐oscillations appear have been determined, and the principal regularities of this regime of deformation are described. The following factors are critical for the appearance of self‐oscillation: speed of straining and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 4 publications
2
32
0
Order By: Relevance
“…Model parameters, such as E 0 , E 1 , η 0 , η 1 , ε c and ε f 0 can be calculated from Equation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). If σ 0 is known E 0 can be determined from Equation (8) and solving the Equation (18) τ 0 can be obtained: (18) and from Equation (6) η 0 can be calculated.…”
Section: Methods Of Determining the Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Model parameters, such as E 0 , E 1 , η 0 , η 1 , ε c and ε f 0 can be calculated from Equation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). If σ 0 is known E 0 can be determined from Equation (8) and solving the Equation (18) τ 0 can be obtained: (18) and from Equation (6) η 0 can be calculated.…”
Section: Methods Of Determining the Model Parametersmentioning
confidence: 99%
“…The reasons of stress oscillation have not been clarified in the literature and are hotly debated [5]. Among possible explanations one can find local heating caused by orientational elongation [6][7][8][9][10]; oscillation of local deformation rate during necking within a critical stress range [11]; orientation crystallization induced by adiabatic heat formation [12].…”
Section: Introductionmentioning
confidence: 99%
“…At this juncture the authors speculate that the role of the BCD part may be clarified by taking inertia into consideration in a transient analysis of initial neck formation and of the propagation of the neck. It was also speculated that the dip BCD may be causin,the'random or cyclic vibrations known [19,20,23] to a~cpmpany neck propagation in solid filament extension. These problems are discussed in section 5 below.…”
Section: The Inertialess Casementioning
confidence: 99%
“…These waves behind the neck influenced both by the shape of t? (X) and the presence or absense of plasticity hysteresis are probably physically real, possibly accounting for the vibrations known to accompany the neck propagation [19,20,23]. The 1/X(2) curves shown in Fig.…”
Section: At2mentioning
confidence: 99%
“…However the exact mechanism behind this phenomenon remains elusive. Adrianova et al [8] has suggested that the formation of the alternating opaque/transparent zones is related to differential heat diffusion. Temperature at the necking region tends to fluctuate, because of the polymer poor heat conductivity and this causes a reduction in the local elastic modulus of the material, triggering thus stress oscillation.…”
Section: Introductionmentioning
confidence: 99%